Study on oxygen species in the products of co-liquefaction of coal and petroleum residues. (1st December 2022) - Zhou, Xiao-Dong; Wu, Hao; Liu, Jing-Mei; Huang, Xue-Li; Fan, Xing; Jin, Li-Jun; Zhu, Yu-Fei; Ma, Feng-Yun; Zhong, Mei
Abstract: From the view of atom economy, it is important to know the form and apportion of oxygen in products, especially the apportion of oxygen in CO2 during direct coal liquefaction (DCL) and co-liquefaction of coal and petroleum residues (CCPR). Herein, co-liquefaction of Naomaohu lignite with Tahe petroleum residue (THPR) was conducted and the O distribution in liquefaction products including gas, n-hexane soluble (HS), asphaltene and pre-asphaltene (AP), and residue (Res) were analyzed by elemental analyzer, GC, GC-MS, FT-IR and APCI-MS. The results showed that CCPR did not change the oxygen speciation but the O distribution in products. O-containing radicals generated from coal pyrolysis would bind to the alkyl radicals from petroleum residue decomposition during CCPR, resulting in remarked increase in the content of O-containing alkanes. Compared with DCL, the apportion of organic oxygen (HS and AP) was increased by 25.94% during CCPR, and the inorganic oxygen (CO, CO2, H2 O, and Res) was decreased by 7.10%, wherein, CO2 content in inorganic oxygen was reduced by 2.13%. This implies that the CCPR not only significantly enhances the utilization of organic oxygen in coal but also inhibits CO2 generation, which is vital for realizing the goal of carbon peak and neutrality. Graphical abstract: Image 1 Highlights: O-containing radicals generated from NMH would bind to alkyl radicals from THPR during CCPR. Compared with DCL, the apportion of organic oxygen in CCPR product increased by 26%. Apportion of O-containing aromatics in HSCCPR -O was 54% lower than that in HSDCL -O. Apportion of O-containing alkanes in HSCCPR -O was 118% higher than that in HSDCL -O.